Intelligent system for modern cars - 415124 Ananthan Seluerajah (Skudai : Universiti Teknologi Malaysia, 2003)
Project Paper (Bachelor of Electrical Engineering (Mechatronics)) - Universiti Teknologi Malaysia, 2003